Answer:
Step-by-step explanation:
First of all you have to put the zeros into factor form.
y1 = (x + 2)(x - 5)
Notice that the x changes sigh. You say that the zeros are -2 and 5. To get y1 to go to zero, you must make x the opposite sign of what you are given.
Now you have to expand the factored form to get the standard form
y = x^2 + 2x - 5x - 10
y = x^2 - 3x - 10
That's not the right answer.
f(0) = 30 but you have - 10 at the end so you have to multiply the factored form by - 3
-3(f(x)) = -3(x + 2)(x - 5)
-3(f(x)) = -3(x^2 - 3x - 10)
f(x) = -3x^2 + 9x + 30
f(0) = -3(0)^2 + 9(0) + 30
f(0) = 30
The quadratic still has roots of (x +2)(x - 5) but that 3 makes the y intercept = 30.
See the graph below.
Answer:
a. $852.96
Step-by-step explanation:
Answer:
y = -x + 1
Step-by-step explanation:
I graphed the points on the graph below
If this answer is correct, please make me Brainliest!
Answer:
The angle for the top of the triangle is 79. For the right corner would be 56. Then going to the bottom of the blue triangle vertice would be 75. The missing angle next to that one would be 55/
Step-by-step explanation:
U first convert it into improper fraction :
2 7/10
=20+7/10
=27/10
=2.7 ...
Hope it helps !!!